Nerve growth factor promotes expression of costimulatory molecules and release of cytokines in dendritic cells involved in Th2 response through LPS-induced p75NTR. (25th November 2016) - Tan, Hongyi; Pan, Pinhua; Zhang, Lemeng; Cao, Zu; Liu, Ben; Li, Haitao; Su, Xiaoli
Abstract: Introduction : Nerve growth factor (NGF) plays an important role in asthmatic inflammatory responses. However, the effects of NGF on dendritic cells (DCs) in asthmatic inflammation remain unknown. Therefore, we examined the effects of NGF on co-stimulatory molecules and the release of cytokines after ovalbumin (OVA) and a low dose of LPS (low LPS) stimulation of dendritic cells. Methods : Bone-marrow-derived dendritic cells (BMDCs) were collected from 6- to 8-week-old wide or TLR4 −/− mice. BMDCs were treated with OVA and/or low LPS for 12h, and then stimulated with NGF for 24h. ELISA and flow cytometry were performed to measure TSLP, IL-6, IL-10, and IL-12 production and MHCII and CD86 expression on BMDCs. BMDCs were exposed to p75 neurotrophin receptor (p75NTR) inhibitor (TAT-Pep5) or NF-kB inhibitor (QNZ) 30 min prior to NGF 1 h after NGF intervention, the levels of RelA and RelB in cytoplasmic and nuclear were detected by west blot. Co-cultured BMDCs with naïve CD4 + T cells, and ELISA was used to detect IL-4 and INF-γ levels. Results : NGF was found to markedly promote OVA and low LPS-induced expression of MHCII, CD86, secretion of TSLP and IL-6, and Th2-response-stimulating capacity of BMDCs. NGF affected BMDCs through LPS-induced p75NTR expression. TAT-Pep5 or QNZ could attenuate the promotive effect of NGF. Conclusions : NGF facilitates OVA with lowLPS-induced maturation of mouse BMDCs through LPS-up-regulated p75 NTR via activation of NF-κB pathways, providing another mechanism for the involvement of NGF in the Th2 response.